ARENA - Experimentation platform to multi-robot systems on industrial environments - Limeira, Marcelo; Oliveira, André Schneider de (Companion Proceedings of the Brazilian Symposium of Robotics & Latin American Robotics Symposium (SBR/LARS); 2021: Companion Proceedings of the 13th Brazilian Symposium of Robotics & 18th Latin American Robotics SymposiumDO - 10.5753/wtdr_ctdr.2021.18685, 2021)
This work presents ARENA - a platform for experimenting with advanced behaviors in smart warehouses. The proposed method consists of reproducing a reduced-scale warehouse managed by a group of autonomous forklifts, represented by a swarm of microrobots compatible with the ROS (Robot Operating System) architecture. Augmented reality (AR) is used to improve the platform’s resources, allowing it to present features that are unfeasible due to the reduced size of its elements or due to the cost, such as the movement of goods and the implementation of certain sensors.